RD Sharma Jan2021 Maths Solution Class 7 Chapter 7
RD Sharma Jan2021 Maths Solution Class 7 Chapter 7
RD Sharma Jan2021 Maths Solution Class 7 Chapter 7
Algebraic Expressions
1. Identify the monomials, binomials, trinomials and quadrinomials from the following
expressions:
(i) a2
(ii) a2 − b2
(iii) x3 + y3 + z3
(iv) x3 + y3 + z3 + 3xyz
(v) 7 + 5
(vi) a b c + 1
(vii) 3x – 2 + 5
(viii) 2x – 3y + 4
(ix) x y + y z + z x
(x) ax3 + bx2 + cx + d
Solution:
(i) Given a2
a2 is a monomial expression because it contains only one term
(ii) Given a2 − b2
a2 − b2 is a binomial expression because it contains two terms
(iii) Given x3 + y3 + z3
x3 + y3 + z3 is a trinomial because it contains three terms
(v) Given 7 + 5
7 + 5 is a monomial expression because it contains only one term
(vi) Given a b c + 1
a b c + 1 is a binomial expression because it contains two terms
(vii) Given 3x – 2 + 5
3x – 2 + 5 is a binomial expression because it contains two terms
RD Sharma Solutions for Class 7 Maths Chapter 7
Algebraic Expressions
(viii) Given 2x – 3y + 4
2x – 3y + 4 is a trinomial because it contains three terms
(ix) Given x y + y z + z x
x y + y z + z x is a trinomial because it contains three terms
Solution:
(i) Given 3x
3x is the only term of the given algebraic expression.
(ii) Given 2x – 3
2x and -3 are the terms of the given algebraic expression.
3. Identify the terms and also mention the numerical coefficients of those terms:
(i) 4xy, -5x2y, -3yx, 2xy2
(ii) 7a2bc,-3ca2b,-(5/2) abc2, 3/2abc2,(-4/3)cba2
Solution:
(i) Like terms 4xy, -3yx and Numerical coefficients 4, -3
(ii) Like terms (-7a2bc, −3ca2b) and (−4/3cba2) and their Numerical coefficients 7, -3,
(-4/3)
RD Sharma Solutions for Class 7 Maths Chapter 7
Algebraic Expressions
Like terms are (−5/2abc2) and (3/2 abc2) and numerical coefficients are (−5/2) and (3/2)
Solution:
(i) Given a2 + b2 -2a2 + c2 + 4a
The like terms in the given algebraic expressions are a2 and −2a2.
Solution:
(i) Given -12x
The numerical coefficient of x is -12.
(i) −3x2
(ii) 5x2yz
(iii) 5/7x2z
(iv) (-3/2) ax2 + yx
Solution:
(i) Given −3x2
The numerical coefficient of x2 is -3.
(iii) Given5/7x2z
The numerical coefficient of x2 is 5/7z.
Solution:
(i) Given –3y
The coefficient of y is -3.
(vi) Given x3 +1
The coefficient of x3 is 1.
(vii) Given − x2
The coefficient of x2 is -1.
Solution:
(i) Given xy
The numerical coefficient in the term xy is 1.
9. Write the numerical coefficient of each term in the following algebraic expressions:
(i) 4x2y – (3/2)xy + 5/2 xy2
(ii) (–5/3)x2y + (7/4)xyz + 3
Solution:
(i) Given 4x2y – (3/2) xy + 5/2 xy2
RD Sharma Solutions for Class 7 Maths Chapter 7
Algebraic Expressions
10. Write the constant term of each of the following algebraic expressions:
(i) x2y − xy2 + 7xy − 3
(ii) a3 − 3a2 + 7a + 5
Solution:
(i) Given x2y − xy2 + 7xy − 3
The constant term in the given algebraic expressions is -3.
Solution:
(i) Given x = -2, y = -1, z = 3
Consider (x/y) + (y/z) + (z/x)
On substituting the given values we get,
= (-2/-1) + (-1/3) + (3/-2)
The LCM of 3 and 2 is 6
= (12 – 2 – 9)/6
= (1/6)
RD Sharma Solutions for Class 7 Maths Chapter 7
Algebraic Expressions
12. Evaluate each of the following algebraic expressions for x = 1, y = -1, z = 2, a = -2, b
= 1, c = -2:
(i) ax + by + cz
(ii) ax2 + by2 – cz
(iii) axy + byz + cxy
Solution:
(i) Given x = 1, y = -1, z = 2, a = -2, b = 1, c = -2
Consider ax + by + cz
On substituting the given values
= (-2) (1) + (1) (-1) + (-2) (2)
= –2 – 1 – 4
= –7
Solution:
(i) Given 3x and 7x
3x + 7x = (3 + 7) x
= 10x
Solution:
(i) Given 7x3y +9yx3
7x3y + 9yx3 = (7 + 9) x3y
= 16x3y
(ii) Given
12a2b + 3ba2 = (12 + 3) a2b
= 15a2b
Solution:
(i) Given 7abc, -5abc, 9abc, -8abc
Consider 7abc + (-5abc) + (9abc) + (-8abc)
= 7abc – 5abc + 9abc – 8abc
RD Sharma Solutions for Class 7 Maths Chapter 7
Algebraic Expressions
Solution:
(i) Given x3 -2x2y + 3xy2- y3, 2x3- 5xy2 + 3x2y - 4y3
Collecting positive and negative like terms together, we get
= x3 +2x3 - 2x2y + 3x2y + 3xy2 - 5xy2 - y3- 4y3
= 3x3 + x2y - 2xy2 - 5y3
(ii) Given a4 - 2a3b + 3ab3 + 4a2b2 + 3b4, - 2a4 - 5ab3 + 7a3b - 6a2b2 + b4
= a4 - 2a3b + 3ab3 + 4a2b2 + 3b4 - 2a4 - 5ab3 + 7a3b - 6a2b2 + b4
Collecting positive and negative like terms together, we get
= a4 - 2a4- 2a3b + 7a3b + 3ab3 - 5ab3 + 4a2b2 - 6a2b2 + 3b4 + b4
= - a4 + 5a3b - 2ab3 - 2a2b2 + 4b4
Solution:
(i) Given 8a – 6ab + 5b, –6a – ab – 8b and –4a + 2ab + 3b
= (8a – 6ab + 5b) + (–6a – ab – 8b) + (–4a + 2ab + 3b)
Collecting positive and negative like terms together, we get
= 8a – 6a – 4a – 6ab – ab + 2ab + 5b – 8b + 3b
= 8a – 10a – 7ab + 2ab + 8b – 8b
RD Sharma Solutions for Class 7 Maths Chapter 7
Algebraic Expressions
= –2a – 5ab
Solution:
(i) Given x – 3y – 2z, 5x + 7y – 8z and 3x – 2y + 5z
= (x – 3y – 2z) + (5x + 7y – 8z) + (3x – 2y + 5z)
Collecting positive and negative like terms together, we get
= x + 5x + 3x – 3y + 7y – 2y – 2z – 8z + 5z
= 9x – 5y + 7y – 10z + 5z
= 9x + 2y – 5z
(ii) Given 4ab – 5bc + 7ca, –3ab + 2bc – 3ca and 5ab – 3bc + 4ca
= (4ab – 5bc + 7ca) + (–3ab + 2bc – 3ca) + (5ab – 3bc + 4ca)
Collecting positive and negative like terms together, we get
= 4ab – 3ab + 5ab – 5bc + 2bc – 3bc + 7ca – 3ca + 4ca
= 9ab – 3ab – 8bc + 2bc + 11ca – 3ca
= 6ab – 6bc + 8ca
Solution:
Given 2x2 - 3x + 1, 3x2 - 2x and 3x + 7
sum of 3x2 - 2x and 3x + 7
= (3x2 - 2x) + (3x +7)
RD Sharma Solutions for Class 7 Maths Chapter 7
Algebraic Expressions
=3x2 - 2x + 3x + 7
= (3x2 + x + 7)
Now, required expression = 2x2 - 3x + 1+ (3x2 + x + 7)
= 2x2 + 3x2 - 3x + x + 1 + 7
= 5x2 - 2x + 8
Solution:
Given x2 + 2xy + y2, x2 - 3y2and 2x2 - y2 + 9.
First we have to find the sum of x2 - 3y2 and 2x2 - y2 + 9
= (x2 - 3y2) + (2x2 - y2 + 9)
= x2 + 2x2 - 3y2 - y2+ 9
= 3x2 - 4y2 + 9
Now, required expression = (x2 + 2xy + y2) + (3x2 - 4y2 + 9)
= x2 + 3x2 + 2xy + y2 - 4y2 + 9
= 4x2 + 2xy - 3y2+ 9
9. Add a3+ b3 - 3 to the sum of 2a3 - 3b3 - 3ab + 7 and -a3 + b3 + 3ab - 9.
Solution:
Given a3+ b3 – 3, 2a3 - 3b3 - 3ab + 7 and -a3 + b3 + 3ab - 9.
First, we need to find the sum of 2a3 - 3b3- 3ab + 7 and - a3 + b3 + 3ab - 9.
= (2a3 - 3b3- 3ab + 7) + (- a3 + b3 + 3ab - 9)
Collecting positive and negative like terms together, we get
= 2a3 - a3- 3b3+ b3 - 3ab + 3ab + 7 - 9
= a3 - 2b3 - 2
Now, the required expression = (a3 + b3 - 3) + (a3 - 2b3 - 2).
= a3+ a3+ b3- 2b3 - 3 - 2
= 2a3 - b3 - 5
10. Subtract:
(i) 7a2b from 3a2b
(ii) 4xy from -3xy
Solution:
(i) Given 7a2b from 3a2b
RD Sharma Solutions for Class 7 Maths Chapter 7
Algebraic Expressions
= 3a2b -7a2b
= (3 -7) a2b
= - 4a2b
11. Subtract:
(i) - 4x from 3y
(ii) - 2x from – 5y
Solution:
(i) Given - 4x from 3y
= (3y) – (–4x)
= 3y + 4x
12. Subtract:
(i) 6x3 −7x2 + 5x − 3 from 4 − 5x + 6x2 − 8x3
(ii) − x2 −3z from 5x2 – y + z + 7
(iii) x3 + 2x2y + 6xy2 − y3 from y3−3xy2−4x2y
Solution:
(i) Given 6x3 −7x2 + 5x − 3 and 4 − 5x + 6x2 − 8x3
= (4 - 5x + 6x2 - 8x3) - (6x3 - 7x2 + 5x - 3)
= 4 - 5x + 6x2 - 8x3 - 6x3 + 7x2 - 5x + 3
= - 8x3- 6x3 + 7x2 + 6x2- 5x - 5x + 3 + 4
= - 14x3 + 13x2 - 10x +7
= 6x2 - y + 4z + 7
13. From
(i) p3 – 4 + 3p2, take away 5p2 − 3p3 + p − 6
(ii) 7 + x − x2, take away 9 + x + 3x2 + 7x3
(iii) 1− 5y2, take away y3 + 7y2 + y + 1
(iv) x3 − 5x2 + 3x + 1, take away 6x2 − 4x3 + 5 + 3x
Solution:
(i) Given p3 – 4 + 3p2, take away 5p2 − 3p3 + p − 6
= (p3 - 4 + 3p2) - (5p2 - 3p3 + p - 6)
= p3 - 4 + 3p2 - 5p2 + 3p3 - p + 6
= p3 + 3p3 + 3p2 - 5p2- p - 4+ 6
= 4p3 - 2p2 - p + 2
= 5x3 - 11x2 – 4
Solution:
First we have to add 3x2 − 5x + 2 and − 5x2 − 8x + 9 then from the result we have to
subtract 4x2 − 7x + 9.
= {(3x2 - 5x + 2) + (- 5x2 - 8x + 9)} - (4x2 - 7x + 9)
= {3x2 - 5x + 2 - 5x2 - 8x + 9} - (4x2 - 7x + 9)
= {3x2 - 5x2 - 5x - 8x + 2 + 9} - (4x2 - 7x + 9)
= {- 2x2 - 13x +11} - (4x2 - 7x + 9)
= - 2x2 - 13x + 11 - 4x2 + 7x – 9
= - 2x2 - 4x2 - 13x + 7x + 11 - 9
= - 6x2 - 6x + 2
Solution:
First we have to find the sum of 13x – 4y + 7z and – 6z + 6x + 3y
Therefore, sum of (13x – 4y + 7z) and (–6z + 6x + 3y)
= (13x – 4y + 7z) + (–6z + 6x + 3y)
= (13x – 4y + 7z – 6z + 6x + 3y)
= (13x + 6x – 4y + 3y + 7z – 6z)
= (19x – y + z)
Now we have to find the sum of (6x – 4y – 4z) and (2x + 4y – 7)
= (6x – 4y – 4z) + (2x + 4y – 7)
= (6x – 4y – 4z + 2x + 4y – 7)
= (6x + 2x – 4z – 7)
= (8x – 4z – 7)
Now, required expression = (8x – 4z – 7) – (19x – y + z)
= 8x – 4z – 7 – 19x + y – z
= 8x – 19x + y – 4z – z – 7
= –11x + y – 5z – 7
16. From the sum of x2 + 3y2 − 6xy, 2x2 − y2 + 8xy, y2 + 8 and x2 − 3xy subtract −3x2 +
4y2 – xy + x – y + 3.
RD Sharma Solutions for Class 7 Maths Chapter 7
Algebraic Expressions
Solution:
First we have to find the sum of (x2 + 3y2 - 6xy), (2x2 - y2 + 8xy), (y2 + 8) and (x2 - 3xy)
={(x2 + 3y2 - 6xy) + (2x2 - y2 + 8xy) + ( y2 + 8) + (x2 - 3xy)}
={x2 + 3y2 - 6xy + 2x2 - y2 + 8xy + y2 + 8 + x2 - 3xy}
= {x2+ 2x2+ x2 + 3y2- y2 + y2- 6xy + 8xy - 3xy + 8}
= 4x2 + 3y2 - xy + 8
Now, from the result subtract the −3x2 + 4y2 – xy + x – y + 3.
Therefore, required expression = (4x2 + 3y2 - xy + 8) - (- 3x2 + 4y2 - xy + x - y + 3)
= 4x2 + 3y2 - xy + 8 + 3x2 - 4y2 + xy - x + y - 3
= 4x2 + 3x2+ 3y2- 4y2- x + y - 3 + 8
= 7x2 - y2- x + y + 5
17. What should be added to xy – 3yz + 4zx to get 4xy – 3zx + 4yz + 7?
Solution:
By subtracting xy – 3yz + 4zx from 4xy – 3zx + 4yz + 7, we get the required expression.
Therefore, required expression = (4xy – 3zx + 4yz + 7) – (xy – 3yz + 4zx)
= 4xy – 3zx + 4yz + 7 – xy + 3yz – 4zx
= 4xy – xy – 3zx – 4zx + 4yz + 3yz + 7
= 3xy – 7zx + 7yz + 7
Solution:
Let 'E' be the required expression. Then, we have
x2 - xy + y2- x + y + 3 - E = - x2 + 3y2 - 4xy + 1
Therefore, E = (x2 - xy + y2- x + y + 3) - (- x2 + 3y2 - 4xy + 1)
= x2 - xy + y2- x + y + 3 + x2 - 3y2 + 4xy - 1
Collecting positive and negative like terms together, we get
= x2 + x2- xy + 4xy + y2- 3y2 - x + y + 3 - 1
= 2x2+ 3xy- 2y2- x + y + 2
Solution:
By subtracting x – 2y + 3z from 3x + 5y – 7 we can get the required expression,
Required expression = (x – 2y + 3z) – (3x + 5y – 7)
RD Sharma Solutions for Class 7 Maths Chapter 7
Algebraic Expressions
= x – 2y + 3z – 3x – 5y + 7
Collecting positive and negative like terms together, we get
= x – 3x – 2y + 5y + 3z + 7
= –2x – 7y + 3z + 7
20. How much is x2 − 2xy + 3y2 less than 2x2 − 3y2 + xy?
Solution:
By subtracting the x2 − 2xy + 3y2 from 2x2 − 3y2 + xy we can get the required expression,
Required expression = (2x2 - 3y2 + xy) - (x2 - 2xy + 3y2)
= 2x2 - 3y2 + xy - x2 + 2xy - 3y2
Collecting positive and negative like terms together, we get
= 2x2- x2 - 3y2 - 3y2 + xy + 2xy
= x2 - 6y2 + 3xy
21. How much does a2 − 3ab + 2b2 exceed 2a2 − 7ab + 9b2?
Solution:
By subtracting 2a2 − 7ab + 9b2 from a2 − 3ab + 2b2 we get the required expression
Required expression = (a2- 3ab + 2b2) - (2a2 - 7ab + 9b2)
= a2- 3ab + 2b2 - 2a2 + 7ab - 9b2
Collecting positive and negative like terms together, we get
= a2 - 2a2 - 3ab + 7ab + 2b2 - 9b2
= - a2 + 4ab - 7b2
22. What must be added to 12x3 − 4x2 + 3x − 7 to make the sum x3 + 2x2 − 3x + 2?
Solution:
Let 'E' be the required expression. Thus, we have
12x3 - 4x2 + 3x - 7 + E = x3 + 2x2 - 3x + 2
Therefore, E = (x3 + 2x2 - 3x + 2) - (12x3 - 4x2 + 3x - 7)
= x3 + 2x2 - 3x + 2 - 12x3 + 4x2 - 3x + 7
Collecting positive and negative like terms together, we get
= x3- 12x3+ 2x2 + 4x2 - 3x - 3x + 2 + 7
= - 11x3 + 6x2 - 6x + 9
23. If P = 7x2 + 5xy − 9y2, Q = 4y2 − 3x2 − 6xy and R = −4x2 + xy + 5y2, show that P + Q + R
RD Sharma Solutions for Class 7 Maths Chapter 7
Algebraic Expressions
= 0.
Solution:
Given P = 7x2 + 5xy − 9y2, Q = 4y2 − 3x2 − 6xy and R = −4x2 + xy + 5y2
Now we have to prove P + Q + R = 0,
Consider P + Q + R = (7x2 + 5xy - 9y2) + (4y2 - 3x2 - 6xy) + (- 4x2 + xy + 5y2)
= 7x2 + 5xy - 9y2 + 4y2 - 3x2 - 6xy - 4x2 + xy + 5y2
Collecting positive and negative like terms together, we get
= 7x2- 3x2 - 4x2 + 5xy - 6xy + xy - 9y2 + 4y2 + 5y2
= 7x2- 7x2 + 6xy - 6xy - 9y2 + 9y2
=0
Solution:
Given P = a2 − b2 + 2ab, Q = a2 + 4b2 − 6ab, R = b2 + b, S = a2 − 4ab and T = −2a2 + b2 – ab +
a.
Now we have to find P + Q + R + S – T
Substituting all values we get
Consider P + Q + R + S - T = {(a2 - b2 + 2ab) + (a2 + 4b2 - 6ab) + (b2 + b) + (a2 - 4ab)} - (-
2a2 + b2 - ab + a)
= {a2 - b2 + 2ab + a2 + 4b2 - 6ab + b2 + b + a2 - 4ab}- (- 2a2 + b2 - ab + a)
= {3a2 + 4b2 - 8ab + b } - (-2a2 + b2 - ab + a)
= 3a2+ 4b2 - 8ab + b + 2a2 - b2 + ab - a
Collecting positive and negative like terms together, we get
3a2+ 2a2 + 4b2 - b2 - 8ab + ab - a + b
= 5a2 + 3b2- 7ab - a + b
RD Sharma Solutions for Class 7 Maths Chapter 7
Algebraic Expressions
1. Place the last two terms of the following expressions in parentheses preceded by a
minus sign:
(i) x + y – 3z + y
(ii) 3x – 2y – 5z – 4
(iii) 3a – 2b + 4c – 5
(iv) 7a + 3b + 2c + 4
(v) 2a2 - b2 - 3ab + 6
(vi) a2 + b2 - c2 + ab - 3ac
Solution:
(i) Given x + y – 3z + y
x + y – 3z + y = x + y – (3z – y)
(ii) Given 3x – 2y – 5z – 4
3x – 2y – 5z – 4 = 3x – 2y – (5z + 4)
(iii) Given 3a – 2b + 4c – 5
3a – 2b + 4c – 5 = 3a – 2b – (–4c + 5)
(iv) Given 7a + 3b + 2c + 4
7a + 3b + 2c + 4 = 7a + 3b – (–2c – 4)
Solution:
(i) Given the sum of a – b and 3a – 2b + 5 = [(a – b) + (3a – 2b + 5)].
This is subtracted from 4a + 2b – 7.
Thus, the required expression is (4a + 2b – 7) – [(a – b) + (3a – 2b + 5)]
(iii) Given the product of subtraction of x2- y2 + 4xy from 2x2 + y2 - 3xy is given by {(2x2 +
y2 - 3xy) – (x2-y2 + 4xy)}
When the above equation is added to 9x2 - 3y2 - xy, we get
{(2x2 + y2 - 3xy) – (x2 - y2 + 4xy)} + (9x2 - 3y2- xy))
This is the required expression.
RD Sharma Solutions for Class 7 Maths Chapter 7
Algebraic Expressions
Solution:
Given 2x + (5x – 3y)
Since the ‘+’ sign precedes the parentheses, we have to retain the sign of each term in
the parentheses when we remove them.
= 2x + 5x – 3y
On simplifying, we get
= 7x – 3y
2. 3x – (y – 2x)
Solution:
Given 3x – (y – 2x)
Since the ‘–’ sign precedes the parentheses, we have to change the sign of each term in
the parentheses when we remove them. Therefore, we have
= 3x – y + 2x
On simplifying, we get
= 5x – y
3. 5a – (3b – 2a + 4c)
Solution:
Given 5a – (3b – 2a + 4c)
Since the ‘-‘sign precedes the parentheses, we have to change the sign of each term in
the parentheses when we remove them.
= 5a – 3b + 2a – 4c
On simplifying, we get
= 7a – 3b – 4c
Solution:
RD Sharma Solutions for Class 7 Maths Chapter 7
Algebraic Expressions
5. 3x + 2y – {x – (2y – 3)}
Solution:
Given 3x + 2y – {x – (2y – 3)}
First, we have to remove the parentheses. Then, we have to remove the braces.
Then we get,
= 3x + 2y – {x – 2y + 3}
= 3x + 2y – x + 2y – 3
On simplifying, we get
= 2x + 4y – 3
6. 5a – {3a – (2 – a) + 4}
Solution:
Given 5a – {3a – (2 – a) + 4}
First, we have to remove the parentheses. Then, we have to remove the braces.
Then we get,
= 5a – {3a – 2 + a + 4}
= 5a – 3a + 2 – a – 4
On simplifying, we get
= 5a – 4a – 2
=a–2
7. a – [b – {a – (b – 1) + 3a}]
Solution:
Given a – [b – {a – (b – 1) + 3a}]
First we have to remove the parentheses, then the curly brackets, and then the square
RD Sharma Solutions for Class 7 Maths Chapter 7
Algebraic Expressions
brackets.
Then we get,
= a – [b – {a – (b – 1) + 3a}]
= a – [b – {a – b + 1 + 3a}]
= a – [b – {4a – b + 1}]
= a – [b – 4a + b – 1]
= a – [2b – 4a – 1]
On simplifying, we get
= a – 2b + 4a + 1
= 5a – 2b + 1
Solution:
Given a – [2b – {3a – (2b – 3c)}]
First we have to remove the parentheses, then the braces, and then the square
brackets.
Then we get,
= a – [2b – {3a – (2b – 3c)}]
= a – [2b – {3a – 2b + 3c}]
= a – [2b – 3a + 2b – 3c]
= a – [4b – 3a – 3c]
On simplifying we get,
= a – 4b + 3a + 3c
= 4a – 4b + 3c
Solution:
Given -x + [5y – {2x – (3y – 5x)}]
First we have to remove the parentheses, then remove braces, and then the square
brackets.
Then we get,
= – x + [5y – {2x – (3y – 5x)}]
= – x + [5y – {2x – 3y + 5x)]
= – x + [5y – {7x – 3y}]
= – x + [5y – 7x + 3y]
RD Sharma Solutions for Class 7 Maths Chapter 7
Algebraic Expressions
= – x + [8y – 7x]
On simplifying we get
= – x + 8y – 7x
= – 8x + 8y
Solution:
Given 2a – [4b – {4a – 3(2a – b)}]
First we have to remove the parentheses, then remove braces, and then the square
brackets.
Then we get,
= 2a – [4b – {4a – 3(2a – b)}]
= 2a – [4b – {4a – 6a + 3b}]
= 2a – [4b – {- 2a + 3b}]
= 2a – [4b + 2a – 3b]
= 2a – [b + 2a]
On simplifying, we get
= 2a – b – 2a
=–b
11. -a – [a + {a + b – 2a – (a – 2b)} - b]
Solution:
Given -a – [a + {a + b – 2a – (a – 2b)} - b]
First we have to remove the parentheses, then remove braces, and then the square
brackets.
Then we get,
= – a – [a + {a + b – 2a – (a – 2b)} – b]
= – a – [a + {a + b – 2a – a + 2b} – b]
= – a – [a + {- 2a + 3b} – b]
= – a – [a – 2a + 3b – b]
= – a – [- a + 2b]
On simplifying, we get
= – a + a – 2b
= – 2b
RD Sharma Solutions for Class 7 Maths Chapter 7
Algebraic Expressions
Solution:
Given 2x – 3y – [3x – 2y -{x – z – (x – 2y)}]
First we have to remove the parentheses, then remove braces, and then the square
brackets.
Then we get,
= 2x – 3y – [3x – 2y – {x – z – (x – 2y)})
= 2x – 3y – [3x – 2y – {x – z – x + 2y}]
= 2x – 3y – [3x – 2y – {- z + 2y}]
= 2x – 3y – [3x – 2y + z – 2y]
= 2x – 3y – [3x – 4y + z]
On simplifying, we get
= 2x – 3y – 3x + 4y – z
=-x+y–z
Solution:
Given 5 + [x – {2y – (6x + y – 4) + 2x} – {x – (y – 2)}]
First we have to remove the parentheses, then remove braces, and then the square
brackets.
Then we get,
= 5 + [x – {2y – (6x + y – 4) + 2x} – {x – (y – 2)}]
= 5 + [x – {2y – 6x – y + 4 + 2x} – {x – y + 2}]
= 5 + [x – {y – 4x + 4} – {x – y + 2}]
= 5 + [x – y + 4x – 4 – x + y – 2]
= 5 + [4x – 6]
= 5 + 4x – 6
= 4x – 1
Solution:
Given x2 - [3x + [2x - (x2 - 1)] + 2]
First we have to remove the parentheses, then remove braces, and then the square
brackets.
RD Sharma Solutions for Class 7 Maths Chapter 7
Algebraic Expressions
Then we get,
= x2 - [3x + [2x - (x2 - 1)] + 2]
= x2 - [3x + [2x - x2 + 1] + 2]
= x2 - [3x + 2x - x2 + 1 + 2]
= x2 - [5x - x2 + 3]
On simplifying we get
= x2 - 5x + x2 - 3
= 2x2 - 5x – 3
Solution:
Given 20 - [5xy + 3[x2 - (xy - y) - (x - y)]]
First we have to remove the parentheses, then remove braces, and then the square
brackets.
Then we get,
= 20 - [5xy + 3[x2 - (xy - y) - (x - y)]]
= 20 - [5xy + 3[x2 – xy + y – x + y]]
= 20 - [5xy + 3[x2 – xy + 2y - x]]
= 20 - [5xy + 3x2 - 3xy + 6y - 3x]
= 20 - [2xy + 3x2 + 6y - 3x]
On simplifying we get
= 20 - 2xy - 3x2 - 6y + 3x
= - 3x2 - 2xy - 6y + 3x + 20
Solution:
Given 85 – [12x – 7(8x – 3) – 2{10x – 5(2 – 4x)}]
First we have to remove the parentheses, then remove braces, and then the square
brackets.
Then we get,
= 85 – [12x – 7(8x – 3) – 2{10x – 5(2 – 4x)}]
= 85 – [12x – 56x + 21 – 2{10x – 10 + 20x}]
= 85 – [12x – 56x + 21 – 2{30x – 10}]
= 85 – [12x – 56x + 21 – 60x + 20]
= 85 – [12x – 116x + 41]
RD Sharma Solutions for Class 7 Maths Chapter 7
Algebraic Expressions
= 85 – [- 104x + 41]
On simplifying, we get
= 85 + 104x – 41
= 44 + 104x
Solution:
Given xy [yz – zx – {yx – (3y – xz) – (xy – zy)}]
First we have to remove the parentheses, then remove braces, and then the square
brackets.
Then we get,
= xy – [yz – zx – {yx – (3y – xz) – (xy – zy)}]
= xy – [yz – zx – {yx – 3y + xz – xy + zy}]
= xy – [yz – zx – {- 3y + xz + zy}]
= xy – [yz – zx + 3y – xz – zy]
= xy – [- zx + 3y – xz]
On simplifying, we get
= xy – [- 2zx + 3y]
= xy + 2xz – 3y
RD Sharma Solutions for Class 7 Maths Chapter 7
Algebraic Expressions